I will come back for you : a family in hiding during World War II - Russo, Marisabina (New York : Schwartz & Wade, 2011)
A grandmother tells her granddaughter the story of the charm bracelet that represent her own childhood experiences while she and her family tried to evade the Nazis in Italy during World War II.
Preschool-Grade 4
Keywords: Grandmothers -- Fiction; Bracelets -- Fiction; Jews -- Italy -- Fiction; World War, 1939-1945 -- Italy -- Fiction; Italy -- History -- 1914-1945 -- Fiction